2022
DOI: 10.1007/s00348-022-03553-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and application of optical flow in background-oriented schlieren for compressible flows

Abstract: Optical flow provides an opportunity to elevate the resolution and sensitivity of deflection sensing in background-oriented schlieren (BOS). Despite extensive relevant literature within the field of computer vision, there is a lack of proper quantification of its abilities and limitations with regard to the state-of-the-art BOS experiments. Thus, this study performs an assessment of accuracy and resolution limits in different flow field scenarios utilizing background patterns generated with random dot and wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Very few studies have performed a comparison of the two. Recently, Cakir et al (2023) has compared the performance of OF over cross-correlation to measure supersonic flows using Background Oriented Schlieren. They found that the OF-based reconstructions revealed superior characteristics of resolution and sensitivity over cross-correlation.…”
Section: Performance Of the Farneback Algorithm Versus Cross-correlat...mentioning
confidence: 99%
“…Very few studies have performed a comparison of the two. Recently, Cakir et al (2023) has compared the performance of OF over cross-correlation to measure supersonic flows using Background Oriented Schlieren. They found that the OF-based reconstructions revealed superior characteristics of resolution and sensitivity over cross-correlation.…”
Section: Performance Of the Farneback Algorithm Versus Cross-correlat...mentioning
confidence: 99%
“…the obtained image and the background image. Compared to the cross correlation method based on the PIV, the optical flow method had higher resolution and accuracy (Cakir et al 2023),so the optical flow method (Atcheson et al 2008) was chosen in this paper to obtain the displacement field.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Recently, dot tracking and optical flow (OF) methods have been adapted for BOS, in the cases of small local displacement fields Cakir et al (2022); Schmidt and Woike (2021); Rajendran et al (2019a). Dot tracking and OF methods can drastically increase the spatial resolution with OF methods providing pixel level displacement estimations.…”
Section: Introductionmentioning
confidence: 99%